Perilaku Konsumtif Mahasiswa Terhadap Jual Beli Online Dalam Perspektif Islam - Almajid Munthe, Muhammad Fikri; Fauzan, Hasfie (BISMA : Business and Management Journal, 2023)
Consumptive behavior is the activity of buying goods or products that are not needed at all so that they become redundant. Students behave consumptively when shopping online through online shop sites. According to an Islamic economic perspective, consumptive behavior in online shopping makes students shop excessively, causing tabzir and israf attitudes. The purpose of this study is to analyze the factors that cause consumptive behavior in shopping online, the advantages and disadvantages of online shopping, as well as the views of Islamic economics in addressing the consumptive behavior of Accounting Sharia college students at UIN Sumatera Utara. for 2022-2023. This research uses a type of qualitative research and data collection. by conducting interviews (interviews). The results of the study show that there are factors that cause students to behave consumptively, namely internal factors: online shopping motivation, perceptions about online shopping, personality, and lifestyle. External factors: shopping culture and friendship groups. The advantages of online shopping are the ease of finding goods, free shipping vouchers, discounted prices, time efficiency, affordable prices, and digital payment transactions. Disadvantages of online shopping: fraud, late/lost goods, and damage to goods.